Acceptance of pay-as-you-throw solid waste charging methods among urban residents in China - Wanjun Yao; Wanjun Yao; Xinyu Zhou (Frontiers in Environmental Science, 2023)
Aim: Pay-as-you-throw (PAYT) is a recognized waste-charging method commonly used in developed countries to reduce waste effectively and improve resource utilization efficiency. China is currently transitioning from a traditional fixed-fee model to a PAYT model.Method: In this study, a sample of 1,346 urban residents in China is analyzed empirically to investigate their willingness to accept this change and the waste fees they are willing to pay for it.Results: The results indicate that, 1) at present, the proportion of urban residents willing to accept the PAYT charging model is low, accounting for only 54.53%. 2) The average annual cost for residents’ households willing to pay for PAYT is 58.616 RMB, which is relatively low. 3) The main reasons for the residents’ low acceptance of PAYT are behavioral attitudes, social norms, and perceived behavioral control factors. 4) Income and education levels mainly explain the low level of expenses paid by residents.Conclusion: Therefore, we suggest that, in the short term, publicity and education should be used to encourage residents to establish a correct environmental concept and a sense of environmental governance ownership, increase their knowledge of waste recycling and disposal and their awareness of waste charging rules, and thus improve their willingness to accept the PAYT charging model. In the long term, the PAYT charging model should be compatible with the levels of economic development and family education, and residents’ waste charges for PAYT should increase steadily.